Adat sebagai Konsep Kunci dan Siri’ sebagai Konsep Inti Budaya Ugi-Mangkasara - Farah Syah Rezah; Abd. Kahar Muzakkir (SIGn Jurnal Hukum, 2021)
This study aims to understand custom as a key concept and siri’ as the core concept of Ugi-Mangkasara Culture based on a legal anthropological perspective. This study uses a normative approach that focuses on tracing the history of customary law related to the object of the problem. The object of study in this research is documents and manuscripts about Ugi-Mangkasara culture. The analysis used is a qualitative analysis based on the perspective of legal anthropology, so that the object of study can be interpreted and described in a narrative form. The study results show that custom as a key concept and siri’ as the core concept of Ugi-Mangkasara culture is a product of the culture of the Ugi-Mangkasara human child, which is full of values from various dimensions as the identity of the Ugi-Mangkasara human child. For Ugi-Mangkasara human children, respecting customs is a social obligation of the culture owner. Enforcing siri’ is respect for self-respect and human dignity. The values contained in the Ugi-Mangkasara culture can be used as a spirit for human children who own the culture in particular and in general for Indonesian children as part of the Ugi-Mangkasara tribe.